Problems of safety and risk in physical education - Podstawski, Robert; Zwolinska, Danuta; Nowosielska-Swadzba, Danuta (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: One of the methodology issues in Physical Education is providing children with safety. The purpose of this work is to present basic concepts of safety at Physical Education classes. Material & Methods: The issues connected with safety at classes of Physical Education have been discussed in the subsections, each of which focuses on different concepts such as: legal safety regulations, causes of hazards, theoretical models of preventing hazards at P.E. classes, nutrition programs related to exercise’s fulfillment, prevention of heat disorders and dehydration. Results: According to experts’ opinion, the causes of safety hazards at P.E. classes can be divided into three groups: caused by instructor, caused by a student, and finally hazards technical in nature. The number of accidents during P.E. classes is still substantial, and among most common hazards there are the following: fractures of upper and lower limbs, dislocations, contusions, tendonitis, muscle tear and cuts. Curiously, boys experience such injuries more frequently than girls. Conclusions: Even though safety rules at Physical Education classes are defined by specific regulations, children’s absolute safety is never guaranteed. In order to diminish the number of misadventures, instructor is obliged not only to adhere to the norms but also to teach children to safety rules.